Studi Kombinasi Capaian Uci (Universal Child Imunisation) Pada Masa Pandemi Covid-19 Menggunakan Logic Framework Evaluation Di Kabupaten Buleleng - Luh Putu Mylinda Yani; putu dian prima kusuma dewi; Ni Made Karlina Sumiari Tangkas; Lina Anggaraeni Dwijayanti (NERSMID : Jurnal Keperawatan dan Kebidanan, 2022)
In 2020, the Covid-19 pandemic hit the world, precisely in March 2020, the first case of Covid-19 disease was found in Indonesia, which later greatly affected all the life of the Indonesian people. Along with the outbreak of Covid-19 in Indonesia, the government implemented policies in tackling the pandemic by limiting the mobility of the community that also influenced government programs, especially the immunization program in an effort to reach UCI Village. The purpose of the study was to determine the achievements of UCI during the Covid-19 pandemic, which was studied using a logic framework evaluation in Buleleng Regency. This research is a mix method model of concurrent triangulation strategy. This type of research is used to simultaneously obtain data related to UCI's achievements so that it could support quantitative and qualitative data. The results showed that the pandemic did not affect the achievements of UCI villages with the number of UCI villages in Buleleng Regency as many as 147 villages from 148 villages, in which 1 village did not reach UCI not because of the pandemic but because of the cultures of the local community.